2022
DOI: 10.26460/md.v7i1.13604
|View full text |Cite
|
Sign up to set email alerts
|

Pemasaran Media Sosial, Gestalt Merek Dan Loyalitas Pelangan: Studi Empiris Pada Tomohon International Flower Festival

Abstract: Meskipun penggunaan media sosial dalam pariwisata telah menjadi fokus banyak penelitian sebelumnya, peranan media sosial dalam membangun merek festival pariwisata masih membutuhkan kajian lebih lanjut. Penelitian ini bertujuan mengembangkan dan menguji model teoritis yang menjelaskan pengaruh pemasaran media sosial (PMS) terhadap gestalt merek dan loyalitas pelanggan dalam konteks festival pariwisata. Lebih lanjut, penelitian ini menguji pengaruh mediasi gestalt merek terhadap hubungan antara pemasaran media s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
2
12
0
1
Order By: Relevance
“…Mandagi et al (2021) identified four key dimensions of brand gestalt: story, sensescape, servicescape and stakeholder. Subsequent research has further developed the nomological network of brand gestalt, demonstrating that it is a critical determinant of brand attachment (Mandagi et al , 2022), brand attitude (Walean et al , 2023), consumer loyalty (Mandagi and Aseng, 2021; Mandagi et al , 2021; Mandagi, 2023), customer satisfaction and purchase intention (Toding and Mandagi, 2022; Walean et al , 2023).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Mandagi et al (2021) identified four key dimensions of brand gestalt: story, sensescape, servicescape and stakeholder. Subsequent research has further developed the nomological network of brand gestalt, demonstrating that it is a critical determinant of brand attachment (Mandagi et al , 2022), brand attitude (Walean et al , 2023), consumer loyalty (Mandagi and Aseng, 2021; Mandagi et al , 2021; Mandagi, 2023), customer satisfaction and purchase intention (Toding and Mandagi, 2022; Walean et al , 2023).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…gestalt) significantly influences customer behavior, resulting in increased brand loyalty and repeat purchases (Rantung et al , 2023; Rondonuwu and Mandagi, 2023; Walean et al , 2023). Moreover, relevant studies have documented the dimensional effects of brand gestalt on loyalty intentions, including repurchase intention (Mandagi et al , 2022; Mandagi, 2023; Rantung et al , 2023; Walean et al , 2023). For instance, a positive and compelling brand story can enhance patients’ overall satisfaction with their health-care experience, ultimately increasing the likelihood of revisiting the health-care provider.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lefrand S. Pasuhuk, Deske W. Mandagi / Integrating Social Media Marketing and Brand Gestalt: An Empirical Analysis in Educational Institutions Organizations derive value from harnessing social media to bolster marketing endeavors, elevate customer awareness, and foster the growth of virtual brand communities (Warbung dkk. 2023;Mandagi 2023). Recognizing the vast and diverse audience present on these platforms, businesses strategically pivot towards leveraging the expansive user base to broaden their market reach.…”
Section: Introductionmentioning
confidence: 99%
“…This two-way communication is not only instrumental in shaping marketing strategies but is also crucial for fostering a sense of brand loyalty and trust among consumers who increasingly seek authenticity and engagement in their interactions with businesses (Rotty dkk. 2022;Mandagi 2023). As companies navigate the landscape of social media-based marketing, they recognize that the pursuit of growth is intricately tied to their ability to adapt, engage, and resonate with the contemporary consumer within the ever-evolving digital ecosystem (Banjarnahor dkk.…”
Section: Introductionmentioning
confidence: 99%